Sistem Informasi Desa dalam Meningkatkan Pelayanan Publik Berbasis Web - Hazira Maharani; Maria Ulfa (Jurnal Informasi dan Teknologi, 2022)
In this era of globalization, the development of Information Technology is growing very rapidly and making the internet a very important requirement to explore various information needed. Everyone can access or obtain data that is available together through an interconnected network on the Internet. Data and information are also very much needed in the need for information for public services in the village. Lesung Batu Village is one of the government institutions of Lahat Regency, South Sumatra Province that requires public services. Currently, Lesung Batu Village still uses a manual system in service, and conveys information to the public so that the speed and accuracy of information still needs to be improved. This study aims to improve community public services in the village to improve public services. This village information system facilitates the delivery of information and provides services that are easier and faster. The village information system was built using the Hypertext Preprocessor (PHP) programming language with MySQL, Bootstrap and Laravel databases. The system development method used is web engineering, which is a software engineering model used for developing web-based applications. The stages in web engineering are Communication, Planning, Modeling Construction, and Deployment. This research resulted in a mobile web-based village information system that can make it easier for people to find the information needed so that they can improve services, it is proven that the services provided by the Lesung Batu village government are effective, fast and precise.